A systematic review of the genus Chasmodes (Teleostei: Perciformes: Blenniidae) - Javonillo, Robert; Harold, Antony S. (Zootaxa, 2010)
A systematic review of the Atlantic blenniid genus Chasmodes was conducted. Principal components analysis (PCA) of 18 box-truss measurements revealed little variation in overall body shape among the three recognized Chasmodes species. In contrast, PCA of six more standard ichthyological measurements and the number of segmented dorsal-fin rays showed significant differences among the three. The species-level classification presented herein agrees with nomenclature in recently published works. Cladistic analysis of partial 12S rRNA gene sequences indicates Chasmodes is sister to a lineage comprising Hypleurochilus, Scartella, and Hypsoblennius. Based on our conclusions about phylogenetic relationships, we infer that sea-level fluctuations were likely associated with speciation in Chasmodes. Remarks on the critical habitats of these blennies are given.